Elevated concentrations of naturally occurring radionuclides in heavy mineral-rich beach sands of Langkawi Island, Malaysia - Khandaker, Mayeen Uddin; Asaduzzaman, Khandoker; Sulaiman, Abdullah Fadil; Bradley, David Andrew; Isinkaye, Matthew Omoniyi (Elsevier, 2018)
Study is made of the radioactivity in the beach sands of Langkawi island, a well-known tourist destination. Investigation is made of the relative presence of the naturally occurring radionuclide 40K and the natural-series indicator radionuclides 226Ra and 232Th, the gamma radiation exposure also being estimated. Sample quantities of black and white sand were collected for gamma ray spectrometry, yielding activity concentration in black sands of 226Ra, 232Th and 40K from 451 ± 9 to 2411 ± 65 Bq kg− 1 (mean of 1478 Bq kg− 1); 232 ± 4 to 1272 ± 35 Bq kg− 1 (mean of 718 Bq kg− 1) and 61 ± 6 to 136 ± 7 Bq kg− 1 (mean of 103 Bq kg− 1) respectively. Conversely, in white sands the respective values for 226Ra and 232Th were appreciably lower, at 8.3 ± 0.5 to 13.7 ± 1.4 Bq kg− 1 (mean of 9.8 Bq kg− 1) and 4.5 ± 0.7 to 9.4 ± 1.0 Bq kg− 1 (mean of 5.9 Bq kg− 1); 40K activities differed insubstantially from that in black sands, at 85 ± 4 to 133 ± 7 Bq kg− 1 with a mean of 102 Bq kg− 1. The mean activity concentrations of 226Ra and 232Th in black sands are comparable with that of high background areas elsewhere in the world. The heavy minerals content gives rise to elevated 226Ra and 232Th activity concentrations in all of black sand samples. Evaluation of the various radiological risk parameters points to values which in some cases could be in excess of recommendations providing for safe living and working. Statistical analysis examines correlations between the origins of the radionuclides, also identifying and classifying the radiological parameters. Present results may help to form an interest in rare-earth resources for the electronics industry, power generation and the viability of nuclear fuels cycle resources.